2018
DOI: 10.1186/s40425-018-0447-2
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood biomarkers correlate with outcomes in advanced non-small cell lung Cancer patients treated with anti-PD-1 antibodies

Abstract: BackgroundAnti-programmed cell death 1 (PD-1) antibodies have demonstrated improved overall survival (OS) and progression-free survival (PFS) in a subset of patients with metastatic or locally advanced non-small cell lung cancer (NSCLC). To date, no blood biomarkers have been identified in NSCLC to predict clinical outcomes of treatment with anti-PD-1 antibodies.Patient and methodsWe performed an analysis of retrospectively registered data of 157 patients with advanced NSCLC treated with anti-PD-1 antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 43 publications
4
99
0
2
Order By: Relevance
“…5 PD-L1/PD-1 has become a hot area of research in recently years. 6,7 The B7/CD28 family regulates the proliferation and function of T cells as antigen-presenting cells (APCs). In addition, some tumours can evade immune elimination, because of overexpression of PD-L1/PD-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 PD-L1/PD-1 has become a hot area of research in recently years. 6,7 The B7/CD28 family regulates the proliferation and function of T cells as antigen-presenting cells (APCs). In addition, some tumours can evade immune elimination, because of overexpression of PD-L1/PD-1.…”
Section: Introductionmentioning
confidence: 99%
“…(range:[1][2][3][4][5][6][7][8][9][10][11][12]. The median score was used to determine the cut-off value of low or high CD28H expression.…”
mentioning
confidence: 99%
“…Although there are few reports of prognostic factors for mRCC treated with ICIs, several studies have shown the association of some inflammatory markers with the prognosis of patients with various malignant diseases treated with ICIs (Table 3). [97][98][99][100][101][102][103][104][105][106] These reports indicate that the parameters related to inflammation might also have some prognostic impact on patients with mRCC treated with ICIs. Further study is expected to clarify the link between the mechanism of inflammation and the effects of ICIs, and to identify the markers related to inflammation to predict or evaluate the effects of ICIs.…”
Section: Inflammatory Markersmentioning
confidence: 84%
“…Although there are few reports of prognostic factors for mRCC treated with ICIs, several studies have shown the association of some inflammatory markers with the prognosis of patients with various malignant diseases treated with ICIs (Table ) . These reports indicate that the parameters related to inflammation might also have some prognostic impact on patients with mRCC treated with ICIs.…”
Section: Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…Other widely acknowledged prognostic markers for deleterious systemic inflammation include an elevated neutrophil-to-lymphocyte ratio (NLR) and lactate dehydrogenase (LDH). NLR is a marker for the general immune response to various stress stimuli, and it is shown to predict outcome among NSCLC and melanoma patients treated with PD-1 inhibitors [78,[81][82][83][84], and CTLA-4 antibodies [78,83,85,86]. Raised LDH level is a classic inflammatory marker in patients with cancer.…”
Section: Circulating Markersmentioning
confidence: 99%